Caspase Activation, Upregulation of Bax and P53, Downregulation of Bcl-2 and Enhanced Generation of Reactive Oxygen Species Mediate the Anti-proliferative and Anti-migratory Activity of Mefenamic Acid in Breast Cancer Cells - AlZharani, Mohammed Mousa; Almuqri, Eman Abdullah; Ahmed, Mohammed Mubarak; Albatli, Shaikha A; Aljarba, Nada Hamad; Rudayni, Hassan Ahmed; Yaseen, Khadijah Nasser; Alkahtani, Saad Hussin; Nasr, Fahd Ali; AlDoaiss, Amin Abdullah; AlEissa, Mohammed Saad (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) are among the most prescribed pharmaceuticals worldwide. Similar to other NSAIDs, mefenamic acid possesses anti- inflammatory, analgesic and antipyretic properties. The present study was carried out to further elucidate the antiproliferative activity of mefenamic acid at the molecular level in the human breast cancer cell line (MCF-7). Materials and Methods: The cytotoxic effect of mefenamic acid on breast cancer cells (MCF-7) was assessed using MTT cytotoxicity and Lactate Dehydrogenase (LDH) leakage assays. qRT-PCR analysis was employed to evaluate the expression of the apoptosis-related genes encoding p53, caspases-3, -8 and-9, Bax and Bcl-2. The anti-migratory effect of mefenamic acid on breast cancer cells was evaluated by using the scratch assay. H2DCFDA (H2-DCF, DCF) cellular assay was employed to estimate the intracellular generation of Reactive Oxygen Species (ROS) in breast cancer cells. Results: A significant decrease in the viability (survival rate) of MCF-7 cells was revealed by MTT cytotoxicity and LDH release assays. Compared to the untreated control cells, there were over-expression of p53, caspases-3, -8 and-9 activities. Bax was significantly upregulated and conversely, Bcl-2 showed significant downregulation. Mefenamic acid significantly inhibited the migration of MCF-7 cells as evidenced by the relatively increased distance between the opposing scratch edges. Comparatively, mefenamic acid enhanced the intracellular generation of ROS in breast cancer cells. Conclusion: Based on the present findings, it was concluded that mefenamic acid can exert anti-proliferative and anti-migratory activity in the human breast cancer cell line. Mefenamic acid could be considered a promising anti-cancer agent in combination with other therapies in the treatment of breast cancer.
Keywords: Antimigratory; Antiproliferative; Breast cancer cells; Cytotoxicity; Gene expression; Mefenamic acid